Nursing experience of treating a critical ill patient with novel coronavirus (2019-nCoV) infected pneumonia by using ECMO - Jing MA; Fen HU; Hui-Min SUN; Jie CHEN; Xin-Bo DING; Jin LI (Yixue xinzhi zazhi)
Most of the new coronavirus (2019-nCoV) infected pneumonia patients have good prognosis, and a few patients are critically ill. As the treatment unit for 2019-nCoV infected pneumonia patients, Zhongnan Hospital of Wuhan University has successfully used the extracorporeal membrane oxygenation (ECMO) technology to save the life of a critically ill patient with 2019-nCoV infected pneumonia. It is also the first successful case of rescue using ECMO technology in Hubei Province. The present article summarized the main treatment process and nursing experience of the successful case.